THE EFFECT OF ZISWAF FUND RECEIPTS, BOPO, AND NON-OPERATIONAL PROFIT/LOSS ON MURABAHAH RECEIVABLES WITH FIRM SIZE AS A MODERATING VARIABLE FOR THE PERIOD OF 2018.Q1 – 2023.Q3 - Akhmad Baha'udin Zuhri; Eka Wahyu Hestya Budianto (Universitas Tulungagung, 2024)
Using company size as a moderating variable, this study examines the effects of Zakat, Infaq, Sadaqah, Waqf (ZISWAF), Operating Costs to Operating Income (BOPO), and Non-Operating Profit/Loss (NOPL) on Murabahah Financing from 2018Q1 to 2023Q3. Multiple regression models are used in this study's quantitative methodology to test the hypothesis. The findings indicated that whilst company size had a large negative impact on murabahah financing, ZIS, BOPO, and NOPL had a considerable beneficial impact. By offering actual data on the effects of ZIS, BOPO, and NOPL on Murabahah Financing as well as the moderating role of Company Size, this study adds to the body of literature. The findings may be useful for financial institutions and policy makers in understanding the determinants of Murabahah Financing and in developing strategies to promote this financing instrument.